Diseño de constructo para marcación de tejido pronéfrico en pez cebra (Danio rerio) (2021)
Zebrafish (Danio rerio) is an ideal animal model for in vivo studies using transgenes of temporary or permanent expression by insertion of constructs into the genome of the organism. This study was aimed to identify the minimum elements for the design and assembly of a transgenic construct for expression in renal precursors and pronephric tissue in this organism. Short sequences of coding and regulatory regions of candidate genes for kidney expression like Pax2.1, Lhx1a, Cdh17 and Atp1a1a.4, were identified including their upstream and downstream elements. Finally, using bioinformatic analysis data from mouse model (Mus musculus) as reference, families of transcription factors like Forkhead, Egr and p53 and some subgroups of families like Hox, Rar and Sox were found as relevant during early kidney development in this animal model. This information is not only relevant to identify evolutionarily conserved regulatory elements but also to contribute to the design of constructs applicable to follow-up early stages of kidney development in zebrafish.